2023
DOI: 10.3390/jof9060691
|View full text |Cite
|
Sign up to set email alerts
|

Succession of Fungal Community during Outdoor Deterioration of Round Bamboo

Xiaojiao An,
Shuaibo Han,
Xin Ren
et al.

Abstract: Bamboo’s mechanical and aesthetic properties are significantly influenced by fungi. However, few studies have been conducted to investigate the structure and dynamics of fungal communities in bamboo during its natural deterioration. In this study, fungal community succession and characteristic variations of round bamboo in roofed and unroofed environments over a period of 13 weeks of deterioration were deciphered using high-throughput sequencing and multiple characterization methods. A total of 459 fungal Oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 92 publications
0
0
0
Order By: Relevance
“…The highest values of bamboo fungal ACE index and Chao 1 index were observed in HY13, with 56.84 and 57.7, respectively. This result was different from our previous research on fresh round bamboo, which showed that community richness presented increasing and declining trends in roofed and unroofed groups, respectively, during deterioration [29]. One of the reasons is that the immersion of an alkaline solution was able to remove some nutrient sources for fungi, such as soluble starch and sugars, forming a barren and harsh environment for microorganisms.…”
Section: Alpha Diversity Analysiscontrasting
confidence: 98%
See 4 more Smart Citations
“…The highest values of bamboo fungal ACE index and Chao 1 index were observed in HY13, with 56.84 and 57.7, respectively. This result was different from our previous research on fresh round bamboo, which showed that community richness presented increasing and declining trends in roofed and unroofed groups, respectively, during deterioration [29]. One of the reasons is that the immersion of an alkaline solution was able to remove some nutrient sources for fungi, such as soluble starch and sugars, forming a barren and harsh environment for microorganisms.…”
Section: Alpha Diversity Analysiscontrasting
confidence: 98%
“…This result indicates that, compared with different rainfall environments, different deterioration times make a greater contribution to the variation of fungal communities and thus have a greater impact on the succession of fungal communities on round bamboo. This result was in accordance with our previous research on fresh round bamboo [29]. In addition, samples of roofed groups (i.e., H9-1, H9-2, and H9-3) were clustered into one branch, while samples of unroofed groups (i.e., HY9-1, HY9-2, and HY9-3) were clustered into another branch in UPGMA dendrograms, which illustrated that rainfall, to some extent, contributes to this divergence.…”
Section: Beta Diversity Analysissupporting
confidence: 94%
See 3 more Smart Citations